Preface: The 4th International Conference on Environmental Resources Management (ICERM) 2021. Issue 1 (1st September 2022) - Haryono, Eko; Keller, Lars; Stötter, Johann; Takahashi, Makoto; Gomez, Christopher; Lassa, Jonatan
Abstract : Landscape is very dynamic [1, 2, 3]. In line with the development of an increasingly climate change [4] and high population, the dynamics of the landscape have also changed due to an increase in the intensity of the population in utilizing land. The condition of the corona virus pandemic since the beginning of 2020 has resulted in two impacts to the environment. On the one hand it has provided a positive impact in the form of improving environmental conditions due to reduction on population mobility and natural resources exploitation, but on the other hand it has also increased the number of dangerous waste, e.g. increasing mask waste accumulation. The Faculty of Geography Universitas Gadjah Mada, Yogyakarta-Indonesia, notably the Department of Environmental Geography has been working for a long time on environmental issues. In order to highlight the topic of environmental resource management in the global region and to broaden perspectives on this subject, the Faculty will organize the 4th International Conference on Environmental Resources Management in Global Region (ICERM). List of ICERM 2021 Committee are available in this pdf.